2017
DOI: 10.14742/ajet.2791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between internet self-efficacy and internet anxiety: A nuanced approach to understanding the connection

Abstract: The present study makes the case that the individual constituents of internet self-efficacy -search self-efficacy, communication self-efficacy, organisation self-efficacy, differentiation selfefficacy, and reactive/generative self-efficacy -may be of differential importance in predicting internet anxiety within web-assisted learning environments. Two hundred and eighty-nine undergraduate students enrolled in a blog-centric general education course on child development at a large mid-western university in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 49 publications
(69 reference statements)
2
23
0
Order By: Relevance
“…One concept that is often confused with technostress is computer/internet anxiety (also described as technophobia or cyberphobia). Computer/internet anxiety is mainly related to fear of using technology (Paul & Glassman, 2017;Tekinarslan, 2008); while technostress is a problem of adaptation experienced by individuals when they are unable to cope with challenges associated with the use of technology (Nimrod, 2018;Tarafdar et al, 2015). In addition, technostress is not only related to technology per se, but also to changing requirements in many aspects of learning (e.g., design and delivery of content and instruction, learning process, and assessment) resulting from the use of technology (Jena, 2015;Jung et al, 2012).…”
Section: Theoretical Framework Extant Research On Technostressmentioning
confidence: 99%
See 1 more Smart Citation
“…One concept that is often confused with technostress is computer/internet anxiety (also described as technophobia or cyberphobia). Computer/internet anxiety is mainly related to fear of using technology (Paul & Glassman, 2017;Tekinarslan, 2008); while technostress is a problem of adaptation experienced by individuals when they are unable to cope with challenges associated with the use of technology (Nimrod, 2018;Tarafdar et al, 2015). In addition, technostress is not only related to technology per se, but also to changing requirements in many aspects of learning (e.g., design and delivery of content and instruction, learning process, and assessment) resulting from the use of technology (Jena, 2015;Jung et al, 2012).…”
Section: Theoretical Framework Extant Research On Technostressmentioning
confidence: 99%
“…Indeed, technology-enhanced learning such as MOOCs, blended learning, and the flipped classroom have potential to afford students personalised learning experience, widen their access to quality learning resources, and innovate their ways of knowledge building and acquiring (Brooker, Corrin, De Barba, Lodge, & Kennedy, 2018;Tuapawa, 2017). However, this new learning mode often incurs demands of more time, knowledge, and skills, and consequently psychological strains for students (Jung, Kudo, & Choi, 2012;Paul & Glassman, 2017). As a result, university students could experience technostress, which is defined as a modern disease of maladaptation caused by individuals' inability to cope with new technology and changing cognitive and social requirements related to the use of technology (Brod, 1984;Ragu-Nathan, Tarafdar, Ragu-Nathan, & Tu, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This claim is supported by [32] which also found that digital divide happens among students. Having this challenge of IT incompetency leads to internet anxiety hence will interrupt the online learning [18,22]. 6.…”
Section: Participants Indicated the Challenge Of Lacking In Itmentioning
confidence: 99%
“…Instructors must also undergo adequate training to develop suitable learning materials for the students [17]. Nonetheless, the need for online learning has increased due to its impressive features: capability to reach global audiences [18], and its unique functionality [11], accessibility [9] and flexibility [19]. The online learning is believed to be one of a complementary means not only to support conventional classroom learning, but also to instill the idea of lifelong learning [20].…”
Section: Introductionmentioning
confidence: 99%
“…For creating a constructivist learning environment by utilizing the resources of the web, it is very essential to seek insight into the relationship between internet self-efficacy and internet anxiety (Paul and Glassman 2017). As internet self-efficacy moderates the relationship between internet anxiety and internet identification so educators and parents should identify students' level of internet self-efficacy and encourage them to gain more knowledge and training about internet usage to boost their internet self-efficacy accordingly (Hsiao et al 2017).…”
Section: Discussionmentioning
confidence: 99%